Progress of tanshinone IIA against respiratory diseases: therapeutic targets and potential mechanisms - Ding, Zhaohui; Deng, Youlin; Luo, Huie; Liu, Cuiwang; Yang, Minjuan; Xue, Hanrong; Chen, Zhengtao (Frontiers in Pharmacology, 2025)
The respiratory system stands as one of the eight pivotal systems within the human body, responsible for a range of essential functions. Primarily, it facilitates the absorption of oxygen from the external environment and the expulsion of carbon dioxide, thereby playing a crucial role in regulating the body’s acid-base balance. Furthermore, it helps to maintain the stability of the internal environment, ensuring the smooth progression of normal metabolic processes and sustaining life activities. In the wake of the novel coronavirus pneumonia outbreak, respiratory diseases have continued to exhibit comparatively high morbidity and mortality rates, underscoring the urgent need for the discovery of novel therapeutic agents. Tanshinone IIA (Tan IIA), a bioactive chemical constituent derived from Salvia miltiorrhiza Bunge, has emerged as a promising candidate. As a significant fat-soluble compound, Tan IIA has traditionally been utilized in the treatment of cardiovascular diseases. As research on Tan IIA has progressed, its multifaceted therapeutic potential has been unveiled. Specifically, Tan IIA has demonstrated anti-inflammatory, anti-oxidative stress, anti-fibrosis, and anti-cancer effects. In recent years, a wealth of studies has concentrated on elucidating its impact on various respiratory diseases, including asthma, chronic obstructive pulmonary disease, pulmonary hypertension, pulmonary fibrosis, acute lung injury/acute respiratory distress syndrome, and lung cancer. These findings collectively suggest that Tan IIA holds considerable promise in the realm of anti-respiratory disease therapies. The present article undertakes a comprehensive review of the targets and potential mechanisms of Tan IIA against respiratory diseases, offering valuable insights that can serve as a reference for future research endeavors and clinical applications of Tan IIA in the treatment of respiratory ailments.